2017
DOI: 10.1093/geront/gnx098
|View full text |Cite
|
Sign up to set email alerts
|

“How Old Do You Feel?” The Difficulties and Ethics of Operationalizing Subjective Age

Abstract: This article provides an integrative presentation regarding ageism within the professional culture of gerontological research by examining the operationalization of subjective age, a construct most commonly assessed by asking an individual to report how "old" they feel. According to the life span perspective [Baltes, P. B. (1987). Theoretical propositions of lifespan developmental psychology: On the dynamics between growth and decline. Developmental Psychology, 23, 611-626] and the life course perspective [Eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…We found that the included dispositional and well-being variables explained only 10% of variance in SA. The low correlation with other subjective ageing measures and the low proportion of explained variance resonate with the ongoing debate about what SA actually measures (Gendron et al 2018 ; Zacher and Rudolph 2018 ). SA can be regarded as a highly aggregated construct that is presumably based on personal experiences of ageing in many different domains (e.g.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We found that the included dispositional and well-being variables explained only 10% of variance in SA. The low correlation with other subjective ageing measures and the low proportion of explained variance resonate with the ongoing debate about what SA actually measures (Gendron et al 2018 ; Zacher and Rudolph 2018 ). SA can be regarded as a highly aggregated construct that is presumably based on personal experiences of ageing in many different domains (e.g.…”
Section: Discussionmentioning
confidence: 72%
“…Despite some evidence to the contrary, however, there remains some controversy about whether “subjective ageing” truly represents a unique construct distinct from people’s general tendency to see things in a positive/negative light or their well-being (cf. Gendron et al 2018 ; Jung and Siedlecki 2018 ; Wurm et al 2007 ). Furthermore, to date there has been little stringent theoretical elaboration regarding the extent to which the SA, ATOA and AgeCog measures tap into the same or different aspects of subjective ageing (though see Diehl et al 2014 for a recent exception), nor has any study empirically examined the extent to which the three measures actually converge (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 Gendron and colleagues suggest that studies such as this one indicate that subjective age is likely an indicator of the degree to which someone has internalized ageism and that asking participants to consider how old they feel may be perpetuating ageist messages. 7 They pose the following thought experiment: imagine that you asked research participants, “how female do you feel” or “how white do you feel?” Without asking follow-up questions, would you know how to interpret their responses? Would those questions yield meaningful data, and would you know what you were measuring?…”
mentioning
confidence: 99%
“…Would psychotherapists encourage patients to consider the many ways in which they live vibrant, active lives and thus challenge their beliefs that they are “old?” This type of intervention assumes that perceiving oneself as older is necessarily negative. Gendron and colleagues 7 suggest that we consider: “What does old feel like? Is feeling old intended to capture the accumulation of wisdom, life experience, and knowledge, or is feeling old intended to capture physical and/or mental decline?” Would intervening to reduce someone's subjective age send a message that feeling older is something to avoid?…”
mentioning
confidence: 99%